INTRODUCTION AND ASSISTANCE OF UTILIZING BUSINESS MARKETING DESIGN APPLICATIONS WITH CANVA FOR TRAINING PARTICIPANTS AL FIRDAUS COMMUNITY WORK TRAINING CENTER (BLKK) KEMNAKER, PANGALENGAN VILLAGE, BANDUNG - Uus Rustiman; Sutiono Mahdi; Ade kosasih (Yayasan Education and Social Center, 2021)
The purpose of this activity is to provide insight to the training participants of the Al Firdaus Kemnaker Community Work Training Center (CWTC) in Pangalengan District in using social media as a means of promotion, especially in creating content with the Canva application. The use of social media is not only about posting product photos but also how to package the product content to make it attractive and have bargaining value. The problem that is often experienced by business actors in using social media is to create interesting and easy content. Efforts to provide a way to create content that is easy and interesting is to use applications that offer templates. One application that can be used is to use Canva. With Canva, businesses can create content with a selection of available templates, create logos, posters, info graphics, newsletters, featured image blogs, invoices, Youtube thumbnails and packaging designs. In the implementation of this introduction and mentoring, the implementation was carried out using the discussion method to map the problems faced by the training participants of the Al Firdaus Kemnaker Community Work Training Center (CWTC) in Pangalengan District in the use of social media. This discussion is used to map the extent of the problems in creating content and using Canva as well as by providing training and mentoring. The activity assistance was attended by around 16 participants from representatives of business actors in Pangalengan sub-district, Bandung Regency, who are members of the UMKM Association of Community Work Training Center (CWTC) al Firdaus Ministry of Manpower in Pangalengan District. The end result of this activity is that participants have an overview of using Canva. In addition, it is hoped that this activity can motivate UMKM actors to market their products more broadly by utilizing the existing marketplace and to innovate and modify their products so that their businesses are more advanced and developed.